Preoperative Ultrasonographic Prediction of Hamstring Tendon Diameter for Anterior Cruciate Ligament Repair - Rodriguez-Mendez, Luis Manuel; Martinez-Ruiz, Jose de Jesus; Perez-Manzo, Ruben; Corona-Hernandez, Jorge Luis; Alcala-Zermeno, Juan Luis; Sanchez-Enriquez, Sergio (The Journal of Knee Surgery, 2017)
The incidence of anterior cruciate ligament (ACL) injuries is rising every year. The autologous hamstring tendon graft, using semitendinosus tendon (SMT) and gracilis tendon (GR), is a common repair technique in the management of ACL injuries due to its multiple advantages. Using a final graft with a minimum diameter of 8 mm is necessary to avoid graft failure. The aim of this study was to find a correlation between preoperative ultrasound (USG) measurement of the SMT and GR tendon diameters (SMTd and GRd) and their actual diameters measured during the grafting procedure. In the present study, 33 male patients aged between 16 and 43 years with ACL injury that required grafting were enrolled. Before the grafting procedure, we sonographically measured the SMTd, GRd, and calculated the hamstring tendon diameter (SMTd + GRd) as the sum of these two. During surgery, we obtained the SMTd, GRd, and SMTd + GRd; we also obtained the length of both tendons and the final graft diameter (FGd). We then compared the obtained values. Mean age was 25.6 ± 7.9 years in our study population. The mean SMTd, GRd, and SMTd + GRd obtained by USG versus transoperatively were 4.9 versus 4.7 mm, 4.3 versus 3.8 mm, and 9.3 versus 8.6 mm, respectively. The mean of FGd was 8.4 mm and the mean length of both tendons was 14.2 cm. The GRd obtained by USG positively correlated with SMTd, SMT tendon length, GRd, and SMTd + GRd (r = 0.460, 0.404, 0.411, and 0.508, respectively). USG-obtained GRd predicts a final tendon diameter < 8 mm (high risk of failure) with a sensitivity, specificity, positive predictive value, and negative predictive value of 100, 54, 28 and 100%, respectively, using 4.5 mm as cutoff. Of all obtained grafts, 85% were deemed adequate (≥ 8 mm) using transoperative measurement, while 91% were ≥ 8 mm using USG measurement. The USG measurement of hamstring tendons is a useful method to predict their transoperative diameter. GRd obtained by USG is the best predictor of transoperative GRd and SMTd + GRd.
Keywords: graft; prediction; hamstring; graft diameter; ACL; USG